Report and Recommendations for Open Educational Resources (OER) Initiatives and Affordable Alternatives at uOttawa - Open & Affordable Learning Materials Working Group (Université d'Ottawa | University of Ottawa, 2021)
Created in late 2019, the OALM Working Group had the mandate to 1) develop awareness and promote the use of affordable course content; 2) explore and recommend strategies to establish an environment at uOttawa in which the creation and adoption of OER is encouraged and rewarded; and 3) coordinate efforts among key campus stakeholders who lead and support open education initiatives on campus. Its report concludes twelve months of work and builds on existing open access and e-learning initiatives. It presents four categories of recommendations to guide open education and textbook affordability activities at uOttawa for the next five years.
Keywords: Open educational resources; Textbook affordability; Affordable course materials; Open education